If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 + -6x = 3x + 19 Reorder the terms: 65 + -6x = 19 + 3x Solving 65 + -6x = 19 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 65 + -6x + -3x = 19 + 3x + -3x Combine like terms: -6x + -3x = -9x 65 + -9x = 19 + 3x + -3x Combine like terms: 3x + -3x = 0 65 + -9x = 19 + 0 65 + -9x = 19 Add '-65' to each side of the equation. 65 + -65 + -9x = 19 + -65 Combine like terms: 65 + -65 = 0 0 + -9x = 19 + -65 -9x = 19 + -65 Combine like terms: 19 + -65 = -46 -9x = -46 Divide each side by '-9'. x = 5.111111111 Simplifying x = 5.111111111
| 2x^2-2+5.5=2 | | 4x^2-20x+19=0 | | y=2x^2+8+6 | | 4+2x+2=2x | | y-1+2y-5=3y-9 | | 0.20(6)+0.05x=0.10(24+x) | | 3x(x-2)(2x+1)=0 | | -99-8=7x+21 | | 7-10x=131-38x | | 103-3x=15x+23 | | .44y^2+1=0 | | 3(y+2)-2=2(4-y) | | 3(y+2)-2=2(41y) | | 5s-19s=28 | | 4t+3=t-18 | | 8+2x*3=x*4+12 | | a^2x+3x=2a^2 | | x^2-5.75+7.75=6 | | x^2-5.75+7.75=1 | | x^2-5.75+7.75=4 | | x^2-5.75+7.75=2 | | 2x^2-4x+8.8=2 | | 2x^2-4x+18.2=2 | | 5a^2-6a=1 | | (10b-6)-3(3b+2)=-3 | | x^2-8x+15.75=0 | | y=0(0)-7 | | (4y+9)(4y+9)=64y^3+432y^2+972y+729 | | 5c+6=2-y | | 5x+6x+3+8=3x+5+7x | | 16+-8-9= | | z^2-8z-20= |